“We Can’t Paint Them with One Brush”: Creating Opportunities for Learning about Refugee Integration - Lam, Michelle (Refuge, 2018)
This article presents the process of creation and initial outcomes of a pedagogical tool called Refugee Journeys: Identity, Intersectionality and Integration, which allows players the opportunity to experience settlement and integration from the identity of a refugee. The purpose of the tool is to educate players about the need for intersectional approaches to refugee service provision, to foster a sense of admiration and respect for refugees’ experiences, and to interact with public policies from the perspective of the least privileged. Outcomes involve recognitions that individual identities affect integration experiences and meaningful discussions about refugee integration, identity, and discrimination.